The effects of health Qigong Baduanjin on the prevention, treatment, and recovery of COVID-19 - Yi-Zhen Han; Meng-Wei Fu; Zi-Jie Chen; Fei-Hong Ren; Dan-Dan Xie; Jing-Lei Li; Si-Yu Zhao; Qian Shen (Wolters Kluwer Medknow Publications, 2020)
To summarize the application and modern studies on health Qigong Baduanjin by domestic and foreign scholars, combined them with clinical practice of mobile hospital in Wuhan, we explore the prevention, treatment, and recovery of Baduanjin in the war against COVID-19. On the basis of studying ancient classics, such as Huangdi's Internal Classic, and the concrete exercise methods of Baduanjin, we propose three ideas: prevention before disease onset, promoting healing during illness, and strengthening the body after recovery. We aimed to give full play to Baduanjin in the battle against COVID-19 to popularize correct prevention and health knowledge for the patients and the healthy as well as to provide a reference for medical workers to use Traditional Chinese Medicine to prevention and treatment.